Enhancement of effectiveness of policies to promote the technological innovation by businesses - Xuyen, Nguyen Huu; Hai Ha, Do Thi; Tuan, Nguyen Quang (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Technological innovation has become a leading priority and decisive factor for success of businesses in market economy and prosperous development of the nation. In practice, however, for successful technological innovation, in addition to their own capabilities, businesses need State support to reduce risks in innovation process. Through qualitative and quantitative studies and use of primary and secondary data, this study is to show clearly: (i) Overview of effectiveness of policies to promote technological innovation by businesses, (ii) Assessment of effectiveness of policies to promote technological innovation by businesses through feedbacks from Hanoi businesses as beneficiaries of these policies, and (iii) Proposal of solutions to enhance effectiveness of policies to promote technological innovation in conformity to Vietnam context. Code: 13081801 <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">